Ideology: A very short instroduction - Freeden, Michael (Oxford Oxford university press, 2003)
Ideology is one of the most controversial terms in the political vocabulary, exciting both revulsion and inspiration. This book examines the reasons for those views, and explains why ideologies deserve respect as a major form of political thinking. It investigates the centrality of ideology both as a political phenomenon and as an organizing framework of political thought and action. It explores the changing understandings of ideology as a concept, and the arguments of the main ideologies. By employing the latest insights from a range of disciplines, the reader is introduced to the vitality and force of a crucial resource at the disposal of societies, through which sense and purpose is assigned to the political world.